THE IMPORTANCE OF ENGLISH FOR PROFESSIONAL DEVELOPMENT IN TECHNICAL FIELDS. - Madumarova Mohinur (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: In today’s globalized world, English serves as the universal language of technology, science, and innovation. Professionals in technical fields— such as engineering, information technology, and applied sciences—need English proficiency to access up-to-date information, participate in international collaboration, and present their research globally. This article examines the importance of English for professional development in technical fields, analyzing relevant literature, methods of language integration in professional education, and the outcomes of English-based training programs.